Challenges in Managing Behavior Variability of Production Control Software - Fang, Miao; Leyh, Georg; Elsner, Christoph; Dorr, Jorg (Proceedings of the 4th International Workshop on Product LinE Approaches in Software Engineering (PLEASE 2013), 2013)
Software product line engineering helps organizations to achieve systematic software reuse by taking advantage of commonalities and predicted variability. Variability management has been considered as one important issue in product line development. In this paper, a variability analysis in production control systems reveals that the variability in such systems lays in the dynamic behavior and interaction of configured components, which we consider as behavior variability. This paper identifies the three main challenges to be solved for applying a product line approach to the domain of production control systems: (1) the selection or design of a proper variability language for describing the flexible behavior variability, (2) the need to model variability of behavior at different levels of granularity, as well as to map the elements among different levels, (3) the binding of behavioral variation points and variants into the various involved systems in a manageable way. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD4.challe
Keywords: Behavior Variability; Product Line Infrastructure; Variability Management